Effect of the organoselenium compound 974zh on the TLR2 and TLR4 gene expression in blood and spleen cells of experimental animals when co-administered with Yersinia pestis EV - A. B. Pyatidesyatnikova; V. I. Dubrovina; O. V. Yurieva; K. M. Korytov; T. I. Ivanova; V. A. Potapov; M. V. Musalov; S. V. Balakhonov (Acta Biomedica Scientifica)
One of the important directions for increasing the immunogenic properties of vaccine strains against highly dangerous infections is the search for adjuvants that not only stimulate the immunological effectiveness of vaccination, but can also provide a metabolic correction of the vaccination process. Organoselenium compounds have immunotropic properties and an antioxidant effect, and therefore, the study of the effect of the organoselenium compound 2,6-dipyridinium-9-selenabicyclo[3.3.1]nonane dibromide (974zh) on the activity of the TLR2 and TLR4 gene expression by macroorganism cells of experimental animals immunized with Yersinia pestis EV NIIEG vaccine strain, is a current area of research.The aim of the work. To assess the TLR2 and TLR4 gene expression by cells of the immune phagocyte system of experimental animals immunized with the Y. pestis EV vaccine strain against the background of immunomodulation with the organoselenium compound 974zh.Materials and methods. The study was carried out on 125 certified outbred white mice. Biological material (blood, spleen) was disinfected, and the spleen was homogenized. RNA isolation and reverse transcription were performed using commercial reagent kits. The expression level of the TLR2 and TLR4 genes was determined using real-time polymerase chain reaction with specific primers.Results. When assessing innate immunity using the example of blood and spleen cells of animal models, features of the TLR2 and TLR4 gene expression were revealed in response to the introduction of the Y. pestis EV vaccine strain against the background of immunomodulation with the 974zh. It was found that 974zh induces a statistically significant increase in TLR2 gene expression when co-administered with Y. pestis EV at a dose of both 104 CFU and 103 CFU.Conclusion. Y. pestis EV against the background of immunomodulation with 974zh, stimulates the expression of the TLR2 and TLR4 genes, which may indicate an increase in the immunogenic properties of the Y. pestis EV vaccine strain under the influence of this preparation.